Fine mapping of qBK1.2, a major QTL governing resistance to bakanae disease in rice - Kushwaha, Amar Kant; Ellur, Ranjith Kumar; Maurya, Sarvesh Kumar; Krishnan S., Gopala; Bashyal, Bishnu Maya; Bhowmick, Prolay Kumar; Vinod, K. K.; Bollinedi, Haritha; Singh, Nagendra Kumar; Singh, Ashok Kumar (Frontiers in Plant Science, 2023)
Bakanae disease caused by Fusarium fujikuroi is an emerging disease of rice causing losses in all rice-growing regions around the world. A BC2F2 population was developed by backcrossing the recurrent parent Pusa Basmati 1121 (PB1121) with the recombinant inbred line RIL28, which harbors a major quantitative trait locus (QTL) governing resistance to bakanae, qBK1.2. MassARRAY-based single-nucleotide polymorphism (SNP) assays targeting the genomic region of qBK1.2 helped in fine mapping the QTL to a region of 130 kb between the SNP markers rs3164311 and rs3295562 using 24 recombinants. In-silico mining of the fine-mapped region identified 11 putative candidate genes with functions related to defense. The expression analysis identified two significantly differentially expressed genes, that is, LOC_Os01g06750 and LOC_Os01g06870, between the susceptible genotype PB1121 and the resistant genotypes Pusa1342 and R-NIL4. Furthermore, the SNPs identified in LOC_Os01g06750 produced minor substitutions of amino acids with no major effect on the resistance-related functional motifs. However, LOC_Os01g06870 had 21 amino acid substitutions, which led to the creation of the leucine-rich repeat (LRR) domain in the resistant genotype Pusa1342, thereby making it a potential candidate underlying the major bakanae-resistant QTL qBK1.2. The markers used in the fine mapping program are of immense utility in marker-assisted breeding for bakanae resistance in rice.